Corporate sustainability and fair market value: a study of Indian family versus non-family firms / Meena Sharma, Raj Kumar and Rajbir Kaur - Sharma, Meena; Kumar, Raj; Kaur, Rajbir (Accounting Research Institute (ARI), 2020)
The recent corporate trends show a shift towards responsible performance and increased responsibility disclosures. The reporting of environmental, social and governance (ESG) factors by a firm has been found to have positive market valuations. This study empirically analyses the association of ESG disclosures and market valuations in an emerging market, India. This study is original as it examines the association between responsibility disclosure and firm value of family firms with non-family business firms. This study was conducted with a sample of 245 Indian companies over 5 years and the results show that ESG disclosures do not significantly explain firm value (measured as Tobin’s q). A significant difference between the ESG disclosure practices of family and non-family firms was found. The family firms make higher ESG disclosures. These results document another advantage of family-ownership in today’s era of responsible investing. The study has implications for investors in investment decision making and screening of investments.